2016
DOI: 10.1002/per.2054
|View full text |Cite
|
Sign up to set email alerts
|

Self–Regulation and Personality Profiles: Empirical Development, Longitudinal Stability and Predictive Ability

Abstract: We used Latent Profile and Latent Profile Transition Analysis to empirically develop and compare competing models of personality profiles (three-and four-profile models). We do so using data from the New Zealand Attitudes and Values Study, a large longitudinal national probability sample of New Zealanders. Both three-and four-profile solutions demonstrated good fit and longitudinal stability. Trait configurations and predictive outcomes of the fourprofile model were the most interpretable in terms of the theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
5
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 70 publications
(113 reference statements)
6
63
5
3
Order By: Relevance
“…Regardless of the labeling issue, it is important to note that Isler et al (2016) also demonstrated consistency in the profile structure within the sample over time. Moreover, using latent transition analysis (LTA), they demonstrated a high degree of within-person consistency.…”
Section: Person-centered Studies Of the Hexaco Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Regardless of the labeling issue, it is important to note that Isler et al (2016) also demonstrated consistency in the profile structure within the sample over time. Moreover, using latent transition analysis (LTA), they demonstrated a high degree of within-person consistency.…”
Section: Person-centered Studies Of the Hexaco Modelmentioning
confidence: 99%
“…More recently, Isler et al (2016) applied LPA to data obtained using the mini IPIP, a 20-item measure of the FFM dimensions from the International Personality Item Pool (IPIP), and 4 additional items to measure Honest-Humility and approximate the HEXACO. The measures were administered on two separate occasions to a randomly selected sample of registered voters in New Zealand.…”
Section: Person-centered Studies Of the Hexaco Modelmentioning
confidence: 99%
See 3 more Smart Citations